Transformasi Industri Dan Pembangunan Industri Terhadap Perekonomian - Eki Indriyanti; Ezar Nafis B; Azizatun Fitriani; Muhammad Yasin (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
In several countries that are classified as developed, the role of the industrial sector is more dominant than other sectors, the industrial sector plays a key role as an engine of economic development. The strategic role of the industrial sector as an engine of economic development is not without reason, because the industrial sector will have derivative impacts, namely increasing the value of capital capitalization, the ability to absorb a large workforce, and the ability to create added value (value added creation) from every input or basic material. which is processed.